STRATEGIES OF READING SKILLS FOR ENGLISH LANGUAGE CLASS - Etty Pratiwi (Universitas PGRI Palembang, 2019)
AbstractÂ The researchers had found that learning reading strategies is a key element in developing student comprehension. However, many teachers lack a solid foundation for teaching these reading comprehension strategies. Therefore, teachers need to be prepared on how to design effective reading comprehension strategies and how to teach these strategies to their students. Therefore this study aims to study the effective reading strategies in order to improve reading skills in language classes. The study is an action research applied to a number of 15 students in an intermediate level integrated skills course. The main question of the study is â€œWould reading strategies help my studentsâ€™ reading comprehension studies?â€. The result od the study indicate that the students had an improvement to a great extend have been tutored about the reading strategies.Â Keyword: reading strategies, predicting, visualizing, inferring, making connections, questioning, action research